Chilling requirement of Ribes cultivars - Jones, Hamlyn G.; Gordon, Sandra L.; Brennan, Rex M. (Frontiers in Plant Science, 2015)
It is usually thought that adequate winter chill is required for the full flowering of many temperate woody species. This paper investigates the sensitivity of blackcurrant bud burst and flowering to natural weather fluctuations in a temperate maritime climate, and compares a range of chill models that have been proposed for assessing the accumulation of winter chill. Bud break for four contrasting cultivars are compared in an exceptionally cold and in a mild winter in Eastern Scotland. The results confirm the importance of chilling at temperatures lower than 0ºC and demonstrate that no single chilling function applies equally to all blackcurrant cultivars. There is a pressing need for further model development to take into account the relationship between chilling temperatures and warming temperatures occurring both during and after the chill accumulation period.